Aggregation-induced emission-active hyperbranched polymer-based nanoparticles and their biological imaging applications. (February 2021) - Kalva, Nagendra; Uthaman, Saji; Jang, Eun Hye; Augustine, Rimesh; Jeon, Su Hyeon; Huh, Kang Moo; Park, In-Kyu; Kim, Il
Abstract: Herein, we developed a facile one-pot approach to prepare amphiphilic aggregation-induced emission (AIE)-active hyperbranched fluorescent nanoparticles with a core–shell structure. This was conducted via the addition reaction between tetraphenylethylene (TPE)-OH, isophorone diisocyanate, and hyperbranched polyglycidol (HPG) using a one-pot method. The resultant AIE-active hyperbranched polymer structure was characterized by 1 H nuclear magnetic resonance and Fourier-transform infrared spectroscopy. The amphiphilic AIE-active polymer was prone to self-assemble in an aqueous solution to form core–shell type nanoparticles with a TPE core and hydroxyl groups on the core surface. The self-assembly of nanoparticles in the aqueous solution was characterized using dynamic light scattering, ultraviolet–visible spectroscopy, fluorescence spectroscopy, and transmission electron microscopy. Aggregation behavior of TPE-HPG polymer in water and diethyl ether was studied by dissipative particle dynamics simulation. Furthermore, these TPE-HPG nanoparticles exhibited a strong blue luminescence in the aqueous solution due to the aggregation of the AIE feature of TPE. These polymeric nanoparticles showed high water solubility, good photostability, and biological imaging properties. The cell viability assay and confocal microscopy imaging results suggested that the TPE-HPG fluorescent polymeric organic nanoparticles (FPNs) have low cytotoxicity and excellent biocompatibility. Thus, TPE-HPG FPNs are excellent candidates for biomedical applications. Graphical abstract: Image 1 Highlights: Aggregation-induced emission (AIE)-active hyperbranched polymer is synthesized. The amphiphilic polymer is self-assembled to form AIE-active nanoparticles (NPs). The AIE-active NPs show excellent water dispersibility and biocompatibility for bioimaging applications.